Several Factors Supporting the Success of Development Extension Strategies in the Agricultural Sector - Ernawati S, K (Asha Publishing, 2025)
Development extension is a communication and learning process aimed at improving community knowledge, skills, and participation in current sustainable development programs. This article aims to analyze the factors supporting the success of development extension strategies in the agricultural sector. A literature review was conducted using various relevant domestic studies. The results of the study indicate that the success of extension programs depends on various factors, including the extension workers, the targets, the methods and media used, the materials delivered, and support from relevant institutions. Extension worker performance is influenced by work experience and available facilities; target characteristics influence the level of participation in the program; methods and media significantly influence innovation adoption; the quality of materials determines the effectiveness of information delivery; and institutional support determines the sustainability of extension programs. Thus, the success of development extension programs cannot be seen from a single aspect but requires cooperation from all parties involved to achieve development goals optimally.